The Use of Pathetic Elements in Beckett’s Endgame - Ismail Radam, Halima (Opción, 2019)
Endgame is a play written by Samuel Beckett and it represents a number of elements that shows pathetic as despair and hopelessness. In addition, there is nothing happening during the play. The fact that the characters are not waiting for anything other than death has heightened the sense of despair and pathetic in the play, plus the feeling of being incarnated after death dominates all the characters. The paper presented sheds light on a number of elements that considered pathetic in the eyes of literary critics.